Minimal positive realizations of linear continuous-time fractional descriptor systems: Two cases of an input-output digraph structure - Markowski, Konrad Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
In the last two decades, fractional calculus has become a subject of great interest in various areas of physics, biology, economics and other sciences. The idea of such a generalization was mentioned by Leibniz and L`Hospital. Fractional calculus has been found to be a very useful tool for modeling linear systems. In this paper, a method for computation of a set of a minimal positive realization of a given transfer function of linear fractional continuous-time descriptor systems has been presented.
Keywords: fractional systems; positive systems; descriptor systems; realization; digraph structure; digraph mask; algorithm